Método baseado em análise envoltória de dados para avaliar a eficiência dos gastos públicos em educação : um estudo de municípios do Estado do Espírito Santo - Alves, Diego Ferreira (2017)
The present study proposes a model of efficiency analysis in public management, focusing on the efficiency of Espirito-santenses Municipalities in applying public resources in education during the year 2015, with emphasis on the evaluation of efficiency in the final years of Elementary School. For this purpose, a DEA model was proposed where DMU and DMV were defined for the problem. Based on this DEA model, educational efficiency scores were measured through Data Envelopment Analysis (DEA). We sought to consider the financial and performance indicators of education and Municipalities. We analyzed 53 Municipalities of Espírito Santo. The results showed that in the period evaluated there were high levels of educational inefficiency. The results indicate that a significant part of the municipalities of the State need to review their public policies directed to education, especially the allocation of resources